Cannibal Tours and Glass Boxes : the Anthropology of Museums. - Ames, Michael M. (UBC Press, 2014)
In "Cannibal Tours and Glass Boxes, " Michael Ames examines the role and responsibility of museums and anthropology in the contemporary world. The author, an internationally renowned museum director, challenges popular concepts and criticisms of museums and presents an alternative perspective which reflects his study of critical social theory and his experience from many years of museum work. Based on the author's previous book, Museums, the Public and Anthropology, this edition includes seven new essays which argue that museums and anthropologists must contextualize and critique themselves--that they must analyse and critique the social, political, and economic systems within which they work. In the new chapters, Ames looks at teh influence of consumerism and the market economy on museums and in the production of such phenomena as the world's fairs and McDonald's hamburger chains, referring to them as 'museums of everyday life.' He also discusses the moral and political ramifications of conflicting attitudes towards Aboriginal art (art or artefact?), censorship (liberating or repressive?), museum exhibits (informative or disinformative?), and postmodernism (a new theory or an old ideology?). The earlier essays outline the development of museums in the Western world, the problems faced by anthropologists in attempting to deal with the often conflicting demands of professional as opposed to public interests, the tendency to both fabricate and stereotype, and the need to establish a reciprocal rather than exploitative relationship between museums/anthropologists and Aboriginal people. Written during the course of the last decade, these essays offer an accessible, often anecdotal, journey through on eprofessional anthropologist's concerns about, and hopes for, his discipline and its future.--